TEACHING METHODS FOR ENGLISH IN PRIMARY EDUCATION - Sharipova Muxabbat Erkinovna (Scholars Digest Publishing, 2024)
This article explores various teaching methods that can be employed in primary education to enhance English language acquisition, focusing on strategies that cater to diverse learning styles and foster a positive learning environment.